2018
DOI: 10.3390/molecules23092371
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK-2 Pathway Inhibition and Tight Junction Protein Upregulation by Catalpol Suppresses Lipopolysaccaride-Induced Disruption of Blood-Brain Barrier Permeability

Abstract: Lipopolysaccaride (LPS) directly or indirectly injures brain microvascular endothelial cells (BMECs) and damages the intercellular tight junction that gives rise to altered blood-brain barrier (BBB) permeability. Catalpol plays a protective role in LPS-induced injury, but whether catalpol protects against LPS-caused damage of BBB permeability and the underlying mechanism remain to be delineated. Prophylactic protection with catalpol (5 mg/kg, i.v.) consecutively for three days reversed the LPS-induced damage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 44 publications
(63 reference statements)
6
47
0
2
Order By: Relevance
“…Nishioku et al reported that pericyte detachment and microglial activation may be involved in the mediation of LPS induced-BBB disruption due to the inflammatory responses in the damaged brain [29]. Our previous in vitro study revealed that LPS destructed the integrity between mice brain microvascular endothelial cells via disaggregating cytoskeleton actin and down-regulating tight junctional proteins, such as claudin-5, occludin, and ZO-1, as well as increasing the secretion of endothelin-1 and inflammatory cytokines secretion [25]. In consistent with our previous results, the disrupted ultrastructure of BBB and the down-regulation of tight junctional proteins were observed in mice after the LPS injury.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Nishioku et al reported that pericyte detachment and microglial activation may be involved in the mediation of LPS induced-BBB disruption due to the inflammatory responses in the damaged brain [29]. Our previous in vitro study revealed that LPS destructed the integrity between mice brain microvascular endothelial cells via disaggregating cytoskeleton actin and down-regulating tight junctional proteins, such as claudin-5, occludin, and ZO-1, as well as increasing the secretion of endothelin-1 and inflammatory cytokines secretion [25]. In consistent with our previous results, the disrupted ultrastructure of BBB and the down-regulation of tight junctional proteins were observed in mice after the LPS injury.…”
Section: Discussionmentioning
confidence: 89%
“…Evans blue perfusion analysis was performed as described previously [25]. At 48 h after the first administration of LPS, mice were intracardially perfused with prewarmed 0.9% NaCl briefly to wash out blood cells, followed by 0.5% Evans blue in cold 4% paraformaldehyde.…”
Section: Evans Blue Perfusion Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Depression symptoms were associated with greater cortisol levels and a more prolonged activation of the HPA axis and with an impaired from psychosocial stressors (Lopez-Duran et al, 2015 ). Under certain situations, stress can increases gut permeability, allowing the gut flora or their metabolites to cross the intestinal mucosa and stimulate the immune-brain system, eventually leading to the activation of immune cells (Feng et al, 2018 ), resulting in microglia activation that is accompanied by depressive-like behaviors (Depino, 2015 ).…”
Section: Microglia Neuroinflammation and Mddmentioning
confidence: 99%
“…This result is very unlikely given the plethora of For (b, c), 232 ≤ N ≤ 244, where N is the number of cells, and for (d, e), N = 12, where N is the number of inserts pooled between the 0d and 1d cAMP conditions. The Mann-Whitney test was used to calculate significant differences for each parameter, where ns = p > 0.05, *p < 0.05, **p < 0.01, ***p < 0.001 and ****p < 0.0001 literary evidence suggesting otherwise [38][39][40][41][42]. Importantly, however, many of these reports are qualitatively correlative between immunostaining and permeability measurement, and not a quantitative correlation between permeability and junction presentation.…”
Section: Transwell Permeability (And Teer) Assays Are Insufficient Fomentioning
confidence: 99%